2022
DOI: 10.1101/2022.02.22.22270838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-month follow-up of heterologous vs homologous third vaccination in kidney transplant recipients

Abstract: Importance Response to SARS-CoV-2 vaccines in kidney transplant recipients (KTR) is severely reduced. Heterologous 3rd vaccination combining mRNA and vector vaccines did not increase seroconversion at four weeks after vaccination but evolution of antibody levels beyond the first month remain unknown. Objective To assess changes in antibody response following a 3rd vaccination with mRNA or vector vaccine in KTR from month one to month three after vaccination. Design, Setting and Participants Three-month follo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Among the 121 studies under full-text review, 98 studies were excluded. Eventually, 23 studies (including 13 published articles and 10 preprints) were included in this meta-analysis based on the inclusion criteria [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 121 studies under full-text review, 98 studies were excluded. Eventually, 23 studies (including 13 published articles and 10 preprints) were included in this meta-analysis based on the inclusion criteria [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“… Risk of bias assessment of the included RCTs [ 14 , 24 , 26 , 27 , 30 , 31 , 35 , 37 , 40 , 41 , 45 ]. …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, an increase in neutralizing antibody response induced by a booster dose against Delta [32,48,67] and Omicron [49,68] variants in the general population and immunocompromised patients has been reported by various authors. Immunocompromised patient populations include kidney transplant recipients [53][54][55][56][57][58][59][60][61]66,[68][69][70] and patients undergoing chronic hemodialysis. [51,57,63,74,76] Although >90 vaccines for COVID-19 are under clinical trials, 23 vaccines have been approved for use in different countries in 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Antibody responses after third or booster dose vaccination among the general population [32,33,39,41,43–45,47–50] and among immunocompromised patients [51–76] have also been evaluated in multiple studies. The waning of immunity against different variants of SARS-CoV-2, such as Delta [16,19,22,25] and Omicron, [28,29] has been reported in several studies.…”
Section: Resultsmentioning
confidence: 99%
“…A new study has found that kidney transplant recipients who receive a heterologous third vaccination combining mRNA and vector SARS‐CoV‐2 vaccines have a seroconversion rate at three months following the third vaccination that is similar to the rate found for a homologous third vaccination. Andreas Heinzel of the Medical University of Vienna in Austria and colleagues found, however, that a heterologous third booster vaccination with the vector vaccine Ad26COVS1 resulted in significantly higher antibody levels in responders 1 …”
Section: Heterologous Third Covid Vaccination May Benefit Kidney Tran...mentioning
confidence: 99%